ANALYZING FIRM PROFITABILITY IN EVALUATING FINANCIAL PERFORMANCE: EVIDENCE FROM AN INDONESIAN MANUFACTURING COMPANY - Wenny Djuarni (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2026)
This research aims to know how the financial performance of PT Mayora Indah Tbk. In This research uses data from the financial statements starting from 2021 to 2025.The research method used is a descriptive qualitative method, data obtained by documentation techniques and literature.and literature. The sampling approach taken is purposive sampling. Based on the results of research that has been done by using the calculation of profitability ratios, namely Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE), at PT Mayora Indah Tbk. Indah Tbk. It can be concluded that the company's financial performance at PT Mayora Indah Tbk after being calculated using the four indicators based on the average of the industry from Kashmir is below the industry average standard. So it can be concluded that the company's financial performance is in “not good”.